Entrevista com Herman Hertzberger - Luiz C. Lara, Fernando; Borges Brasileiro, Vanessa (Cadernos de Arquitetura e Urbanismo, 2024)
Article originally published without abstract. Keywords assigned by the editorial team at the time of digitization.